Ochrona uzupełniająca dla ofiar powszechnej przemocy w sytuacji wewnętrznego konfliktu zbrojnego. Dialog sądów europejskich i jego konsekwencje - Kowalczyk, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article examines the protection afforded in the European Union to victims of internal armed conflicts in the context of Article 15 c of the Qualification Directive 2004 and 2011 and Article 3 of the ECHR. A short analysis of various forms of protection provided for non-convention refugees war refugees in EU law provides a background. The next part analyses the recent case law of the Court of Justice of the EU, important for the interpretation and implementation of Article 15 c of the Directive. Two rulings are commented on in detail: in Elgafaji case and in Diakite case. Jurisprudence of the European Court of Human Rights is also of practical importance for the scope of subsidiary protection. The purpose of this study is to analyze the judicial dialogue and its impact on the predictability of decisions in individual cases.
Keywords: sądy europejskie; ochrona uzupełniająca; ofiary; powszechna przemoc; wewnętrzny konflikt zbrojny